Unravelling the jurisdiction of Provincial High Courts under Article 154 P (4) of the Constitution: A case law review - Puwanitha, S. (University of Colombo, 2025)
Article 154 P (4) of the Sri Lankan Constitution delineates the jurisdiction of the Provincial High Courts (PHCs) in issuing writs. However, the divergent judicial interpretations of this provision - some are devolution-friendly and some are devolution-unfriendly - have created ambiguity in comprehending the jurisdictional scope of PHCs. This study aims to interpret Article 154 P (4) to clarify and categorise the prerequisites for PHCs to exercise writ jurisdiction. This study employs a case law review-based exploratory research and uses qualitative research methods. The findings highlight the judiciary's reliance on two major criteria: (1) the inquiry into the qualitative nature and scope of power exercised by an authority, which contradicts with the objectives of the devolutionary scheme, and (2) the locus from which the power is exercised—whether it emanates from a central authority or a provincial authority. The analysis reveals that judicial interpretations of the jurisdiction of the PHCs have inadequately considered the local nature of the issues, where the expertise of those most familiar with them would be accessible within the PHCs, and failed to align their interpretations with the rationale underlying the introduction of the 13th Amendment. Thus, the study proposes four key prerequisites to determine the jurisdiction of PHCs to adjudicate writ applications by interpreting Article 154 P (4): (1)whether the issue before the PHC deals with any matter in the Provincial Council List; (2) whether the power is derived from any law or provincial statutes; (3) whether the authority was exercised by any persons authorized under any law or statutes; and (4) whether the authority exercised such power within the territorial boundaries. By and large, the study argues that adopting a purposive interpretation of Article 154 P (4) will strengthen the devolutionary objectives of the 13th Amendment and ensure that local disputes are addressed by the institutions best suited to resolve them.
Keywords: Provincial High Courts; Devolution; Article 154P (4); Writ Jurisdiction; 13th Amendment